Nano selenium-enriched probiotic Lactobacillus enhances alum adjuvanticity and promotes antigen-specific systemic and mucosal immunity - Liu, Runhang; Sun, Weijiao; Sun, Tianzhi; Zhang, Wenzhi; Nan, Yongchao; Zhang, Zheng; Xiang, Kongrui; Yang, Hongliang; Wang, Fang; Ge, Junwei (Frontiers in Immunology, 2023)
Nano selenium-enriched probiotics have been identified to improve immune responses, such as alleviating inflammation, antioxidant function, treatment of tumors, anticancer activity, and regulating intestinal flora. However, so far, there is little information on improving the immune effect of the vaccine. Here, we prepared nano selenium-enriched Levilactobacillus brevis 23017 (SeL) and heat-inactivated nano selenium-enriched L. brevis 23017 (HiSeL) and evaluated their immune enhancing functions on the alum-adjuvanted, inactivated Clostridium perfringens type A vaccine in mouse and rabbit models, respectively. We found that SeL enhanced immune responses of the vaccine by inducing a more rapid antibody production, eliciting higher immunoglobulin G (IgG) antibody titers, improving secretory immunoglobulin A (SIgA) antibody level and cellular immune response, and regulating Th1/Th2 immune response, thus helping to induce better protective efficacy after challenge. Moreover, we confirmed that the immunoenhancement effects are related to regulating oxidative stress, cytokine secretion, and selenoprotein expression. Meanwhile, similar effects were observed in HiSeL. In addition, they show enhanced humoral immune response at 1/2 and 1/4 standard vaccine doses, which confirms their prominent immune enhancement effect. Finally, the effect of improving vaccine immune responses was further confirmed in rabbits, which shows that SeL stimulates the production of IgG antibodies, generates α toxin–neutralizing antibodies rapidly, and reduces the pathological damage to intestine tissue. Our study demonstrates that nano selenium-enriched probiotics improve the immune effect of the alum adjuvants vaccine and highlight its potential usage in remedying the disadvantages of alum adjuvants.